DAMPAK OBJEK WISATA BUKIT KASIH TERHADAP PENDAPATAN MASYARAKAT DI DESA KANONANG DUA KECAMATAN KAWANGKOAN BARAT - Meilan Hardina Wowor; Gene H. M. Kapantow; Eyverson ., Ruauw (Sam Ratulangi University, 2018)
This study aims to look at the impact of Bukit Kasih tourism objects on the income of the people of Kanonang Dua Village who did business on the tourist attraction area. This research was carried out for 3 months from namely May to July 2018. The data used was primary data, through direct interviews with 30 respondents, namely those who run businesses in the Bukit Kasih Tourism Area. Secondary data obtained through the internet by using google searching to access scientific journal articles and thesis from other universities that relevant with the research. The sampling technique used was purposive sampling. This study used an analysis of the average difference through the t-test, the impact was measured by comparing income before and after doing business in the tourism area. The results showed that there was a significant increase in income for the people who doing business at the Bukit Kasih Tourism Area. The average income of the community before doing business in the tourist area was Rp. 883,333 per month and increased to Rp. 2,390,000 per month after doing business in the Bukit Kasih Tourism Area. This means that the average income increases by 1.506.667,00,- *ghmk+eprm*